METODOLOGI ANALISIS TEKS BERWAWASAN GENDER: Perspektif Hermeneutik - Iwanebel, Fejrian Yazdajird (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractProblems of women when seen through the eyes of faith will continue to looksexy. Because religion is often considered